International Trade under Threat: Stopping Protectionism Through Institutional Reforms - Georg Erber; Ulrich Thießen (Weekly Report, 2009)
The global economic crisis has led to a massive increase in unemployment, and nearly all governments have declared the protection of domestic jobs to be a central economic policy aim. In the US, an additional 790-billion economic stimulus package was adopted immediately after President Obama took office. The package includes a "Buy American" clause intended to give preferential treatment to domestic suppliers in public procurement, and is leading to countermeasures by other countries. In some cases, there have been tariff increases and trade-distorting currency depreciations. Already the announcement of protectionist measures can have immediate adverse effects on policy decisions elsewhere and one is reminded of the US Smoot-Hawley act of 1930 with its dramatic negative consequences on global trade and economic growth afterwards. Efforts should be made to strengthen multilateral organizations at this moment in the current global crisis. DIW Berlin advocates the reform of the International Monetary Fund. In addition, the G-20 should play a larger role in combating international financial crises. Finally, in the future, the EU should only be represented in the G-20 by a single representative.
Keywords: F13; F32; F51; F53; F59; 330; Buy American Clause; Stimulus package; Protectionism; Trade-barriers